Development and Evaluation of a Mobile App Designed to Increase HIV Testing and Pre-exposure Prophylaxis Use Among Young Men Who Have Sex With Men in the United States: Open Pilot Trial - Biello, Katie B; Hill-Rorie, Jonathan; Valente, Pablo K; Futterman, Donna; Sullivan, Patrick S; Hightow-Weidman, Lisa; Muessig, Kathryn; Dormitzer, Julian; Mimiaga, Matthew J; Mayer, Kenneth H (JMIR Publications, 2021)
BackgroundHIV disproportionately affects young men who have sex with men (YMSM) in the United States. Uptake of evidence-based prevention strategies, including routine HIV testing and use of pre-exposure prophylaxis (PrEP), is suboptimal in this population. Novel methods for reaching YMSM are required. ObjectiveThe aim of this study is to describe the development and evaluate the feasibility and acceptability of the MyChoices app, a mobile app designed to increase HIV testing and PrEP use among YMSM in the United States. MethodsInformed by the social cognitive theory, the MyChoices app was developed using an iterative process to increase HIV testing and PrEP uptake among YMSM. In 2017, beta theater testing was conducted in two US cities to garner feedback (n=4 groups; n=28 YMSM). These findings were used to refine MyChoices, which was then tested for initial acceptability and usability in a technical pilot (N=11 YMSM). Baseline and 2-month postbaseline assessments and exit interviews were completed. Transcripts were coded using a deductive approach, and thematic analysis was used to synthesize data; app acceptability and use data were also reported. ResultsThe MyChoices app includes personalized recommendations for HIV testing frequency and PrEP use; information on types of HIV tests and PrEP; ability to search for nearby HIV testing and PrEP care sites; and ability to order free home HIV and sexually transmitted infection test kits, condoms, and lube. In theater testing, YMSM described that MyChoices appears useful and that they would recommend it to peers. Participants liked the look and feel of the app and believed that the ability to search for and be pinged when near an HIV testing site would be beneficial. Some suggested that portions of the app felt repetitive and preferred using casual language rather than formal or medicalized terms. Following theater testing, the MyChoices app was refined, and participants in the technical pilot used the app, on average, 8 (SD 5.0; range 2-18) times over 2 months, with an average duration of 28 (SD 38.9) minutes per session. At the 2-month follow-up, the mean System Usability Scale (0-100) score was 71 (ie, above average; SD 11.8). Over 80% (9/11) of the participants reported that MyChoices was useful and 91% (10/11) said that they would recommend it to a friend. In exit interviews, there was a high level of acceptability for the content, interface, and features. ConclusionsThese data show the initial acceptability and user engagement of the MyChoices app. If future studies demonstrate efficacy in increasing HIV testing and PrEP uptake, the app is scalable to reach YMSM across the United States. Trial RegistrationClinicaltrials.gov NCT03179319; https://clinicaltrials.gov/ct2/show/NCT03179319 International Registered Report Identifier (IRRID)RR2-10.2196/10694